The lost wreck of the Isis - Ballard, Robert D.; Archbold, Rick, 1950-; McCann, Anna Marguerite (New York, N.Y. : Scholastic/Madison Press Book, 1990)
Dr. Ballard visits the Mediterranean to explore a Roman shipwreck site and investigate an active underwater volcano.
Includes bibliographical references (p. [64]).
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
6.1
5-8
Keywords: Shipwrecks -- Italy -- Sicily -- Juvenile literature; Underwater archaeology -- Italy -- Sicily -- Juvenile literature; Romans -- Italy -- Sicily -- Juvenile literature; Shipwrecks; Underwater archaeology; Archaeology; Romans -- Italy -- Sicily; Shipwrecks; Romans -- Italy -- Sicily; Archeology -- Sicily (Italy); Sicily (Italy) -- Antiquities, Roman -- Juvenile literature; Sicily (Italy) -- Antiquities, Roman; Sicily (Italy) -- Antiquities